Case Report: Rescue “awake” extracorporeal membrane oxygenation for acute respiratory failure in severe granulomatosis with polyangiitis with multisystem involvement - Kim, Taehun; Song, Byung Wook; Shin, Hyeong Chan (Frontiers in Medicine, 2025)
We present the case of a 40-year-old man who developed severe acute respiratory failure along with hemoptysis and was subsequently diagnosed with granulomatosis with polyangiitis (GPA). He was initially treated with high-dose corticosteroids, cyclophosphamide, plasmapheresis, and mechanical ventilation (MV). The patient’s condition deteriorated after being weaned from MV, leading to his transfer to our medical center without reintubation. Upon admission, a high-flow nasal cannula delivering FiO2 of 1.0 was immediately initiated. Despite the severity of hypoxemia, the patient exhibited neither tachypnea nor subjective dyspnea, and was subsequently initiated on “awake” venovenous extracorporeal membrane oxygenation (VV-ECMO) without MV. Anticoagulation therapy was initiated, and continuous renal replacement therapy was commenced to manage anuria associated with acute renal failure. Due to treatment failure after initial immunosuppressive therapy with cyclophosphamide, rituximab was administered as an induction agent. Following four cycles of rituximab, the patient’s respiratory function showed marked improvement. Subsequently, a splenic artery hemorrhage occurred but was effectively managed through prompt embolization, resulting in immediate hemodynamic stabilization. The patient was successfully weaned off VV-ECMO support on day 22 after starting ECMO. After the transfer from the intensive care unit, the patient began active rehabilitation, during which he reported episodes of dizziness. Magnetic resonance imaging of the brain revealed multiple acute infarctions, which are presumed to be caused by vasculitis, leading to the initiation of adjunctive antiplatelet therapy. This represents the first reported case of refractory severe GPA affecting the kidneys, splenic artery, and central nervous system and resulting in respiratory failure, which was managed using “awake” VV-ECMO. The patient remains on maintenance hemodialysis and continues treatment with corticosteroids and rituximab. No disease relapse has occurred until now (June 2025), and the patient is undergoing rehabilitation for intensive care unit-acquired weakness.